Age structure and growth rate of (Squalius cephalus Linnaeus, 1758) in Tuji tributary from Talar River, Mazandaran Province - M.H. Gorjian Arabi email ; S.A. Hosseini; M. Roohi; R. Patimar; S. Vatandust; E. Alijanpour (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2012)
A structure and growth pattern of Squalius cephalus (Linnaeus, 1758) in Tuji tributary of Talar River, Mazandaran Province, was studied during the period from August 2008 till August 2009. In total, 298 fish were caught by electrofishing and fixed in 10% formalin. The weight and length of fish were measured and the age was determinated by scallometric method. The age data showed that fishes were between 0+ to 4+ age groups. Pauli`s applied growth pattern showed a positive alometric for male and female and total fish and a negative isometric for unmature fishes. The average instantaneous growth rate of European Chub showed that the age groups 2+ and 3+ with 1.1 had the fastest growth compare to 3+ and 4+ age groups with 0.89. Condition factor of specimens showed that the highest one with 1.58 (r2 = 0.983) belong to females and the lowest with 1.17 (r2 = 0.901) belong to unmature fishes. The total sex ratio (123 males to 115 females) showed no significant differences between them.